2018
DOI: 10.2169/internalmedicine.0707-17
|View full text |Cite
|
Sign up to set email alerts
|

Phlegmonous Gastritis: A Report of Three Cases with Clinical and Imaging Features

Abstract: Phlegmonous gastritis is a rare but often fatal acute pyogenic infection of the stomach. We herein report three cases of phlegmonous gastritis with different causes: the long-term placement of a nasogastric feeding tube, bacteremia associated with cellulitis in a diabetic patient, and an adverse reaction to paclitaxel/carboplatin chemotherapy for cancer of unknown primary cause, which were classified as primary, secondary, and idiopathic types, respectively. Coping with the increasing morbidity rate associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 16 publications
(20 reference statements)
2
24
0
2
Order By: Relevance
“…APG is most commonly caused by streptococcus, in particular the β-hemolytic Streptococcus group A ( Streptococcus pyogenes ) which is resistant to gastric acid [ 7 ]. Enterobacteriaceae, Staphylococus spp , Haemophilus influenza and endogenous bacteria of the oral cavity are also commonly involved and have been described [ 4 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…APG is most commonly caused by streptococcus, in particular the β-hemolytic Streptococcus group A ( Streptococcus pyogenes ) which is resistant to gastric acid [ 7 ]. Enterobacteriaceae, Staphylococus spp , Haemophilus influenza and endogenous bacteria of the oral cavity are also commonly involved and have been described [ 4 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In up to 41% of the cases, however, no risk factor can be identified [ 7 ]. Proton pump inhibitors and anti-H2 could also contribute to bacterial proliferation by increasing gastric pH [ 3 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent review of 45 cases, no difference on mortality has been observed between antibiotic and surgical treatment [ 1 ]. Duration of antibiotic therapy remains however variable according to the case reports, extending from 7 to 21 days [ 3 , 14 16 ]. Our patient had a favourable outcome with 14 days of a broad-coverage antibiotic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations